IMPLEMENTASI PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Agam, Muchammad Faiz; Handayani, Aprilia Dwi; Mujiono, Mohammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study examines the implementation of the snakes and ladders game to improve students' mathematics learning outcomes at SD Negeri Burengan 3. Using the Classroom Action Research (CAR) method, data were collected from learning outcomes during the pre-cycle and two learning cycles. The researcher employed a research design by Kemmis & McTaggart, which includes the steps of planning, acting, observing, and reflecting. The implementation of this CAR was conducted at SD Negeri Burengan 3, Kediri City. The research was carried out in Grade I for the Elementary School Mathematics subject, specifically on the topic of comparing integers. The class consisted of 26 students, comprising 15 boys and 11 girls. The results of this study showed that before the implementation of the snakes and ladders game, students' learning outcomes were relatively low, with an average score of 61 during the pre-cycle. This improved to 72 in Cycle I and further increased to 83 in Cycle II after improvements were made. Students' classical learning mastery also improved, rising from 31% in the pre-cycle to 62% in Cycle I, and reaching 73% in Cycle II. Thus, these results indicate that the use of the snakes and ladders game successfully helped students understand the concept of number comparison more easily and engagingly. Learning became more interactive, and students were more motivated and active during the learning process. ABSTRAKPenelitian ini mengkaji implementasi permainan ular tangga untuk meningkatkan hasil belajar matematika siswa di SD Negeri Burengan 3. Melalui metode penelitian tindakan kelas (PTK), data dikumpulkan dari hasil belajar selama pra-siklus, dan 2 siklus pembelajaran. Peneliti mengguanakan desain penelitian dari Kemmis & Mc. Taggart dengan langkah-langkah meliputi Perencanaan (plan), Melaksanakan tindakan (act), Melaksanakan pengamatan (observe), dan Mengadakan refleksi / analisis (reflection). Pelaksanaan Penelitian Tindakan Kelas (PTK) ini dilaksanakan di SD Negeri Burengan 3 Kota Kediri. Peneliti mengambil penelitian di kelas I pada mata pelajaran Matematika SD materi perbandingan bilangan cacah. Jumlah siswa kelas I sebanyak 26 anak terdiri dari 15 laki-laki dan 11 perempuan. Pada penelitian ini diperoleh hasil bahwa sebelum menerapkan permainan ular tangga, hasil belajar siswa dapat dikatakan rendah yang semula pada pra-siklus 61 meningkat menjadi 72 di siklus I dan mengalami peningkatan menjadi 83 pada siklus II setelah dilakukan perbaikan. Ketuntasan belajar klasikal siswa mengalami peningkatan dari 31% pada pra-siklus menjadi 62% pada siklus I dan pada siklus II meningkat menjadi 73%. Dengan demikian, hasil ini menunjukkan bahwa permainan ular tangga berhasil membantu siswa dalam memahami materi perbandingan bilangan dengan lebih mudah dan menarik. Pembelajaran menjadi lebih interaktif, siswa lebih termotivasi, serta lebih aktif dalam proses pembelajaran.